Study guides

Q: What is 2x plus 92 plus 6x?

Write your answer...

Submit

Related questions

x + 2x + 6x = 9x

2x + 6x + 4x = 12x

5x + x - 6x + 2x = 2x

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

6x + 9 + 2x = 8x + 9

-2x + 11 + 6x = 4x + 11

2x + x + 2x + x = 6x

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

6x - 9 + 2x + 1 = 8x -8

6x - 8 + 2x - 5 = 7 - 2x ?

6x-52 = 4x+40 6x-4x = 40+52 2x = 92 Answer: x = 46

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

The value of X in the equation 2x-1-6 5 plus 6x is -3.

6x with 3 over the x, because that is how many x's there are.

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

6x

9y - 4x

6x-8+2x-5 = 7-2x 6x+2x+2x = 7+8+5 10x = 20 x = 20/10 x = 2

2x + 4x + 3 = 6x + 3

It is 6x(2x+5) when factored

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

If: 2x+6x-4 = 52 Then: x = 7

6x - 2x + 5x - 3First you want to have the x's by theirselves and the numbers by themselvesIt will still be:6x - 2x + 5x - 3Here, you do 6x - 2x.4x + 5x -3Then you combine 4x + 5x.9x - 3Simplified just like that

6x + 3 = 3(2x + 1)

8x + 9z